2013
DOI: 10.1099/mic.0.066712-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to generate a recombinant toxoid vaccine against Clostridium difficile

Abstract: The Clostridium difficile toxins A and B are primarily responsible for symptoms of C. difficile associated disease and are prime targets for vaccine development. We describe a plasmid-based system for the production of genetically modified toxins in a non-sporulating strain of C. difficile that lacks the toxin genes tcdA and tcdB. TcdA and TcdB mutations targeting established glucosyltransferase cytotoxicity determinants were introduced into recombinant plasmids and episomally expressed toxin mutants purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 40 publications
(56 reference statements)
5
72
0
1
Order By: Relevance
“…41 In addition, trans-membrane domain of TcdB has also been reported to contribute to toxicity. 42 To ensure that mTcd138 was atoxic, 2 amino acids, which have been reported to be the key residues involved in the GT activity, 43,44 were mutated in the GT domain of TcdB (Fig. 1B).…”
Section: Construction and Cytotoxicity Testing Of Mtcd138mentioning
confidence: 99%
“…41 In addition, trans-membrane domain of TcdB has also been reported to contribute to toxicity. 42 To ensure that mTcd138 was atoxic, 2 amino acids, which have been reported to be the key residues involved in the GT activity, 43,44 were mutated in the GT domain of TcdB (Fig. 1B).…”
Section: Construction and Cytotoxicity Testing Of Mtcd138mentioning
confidence: 99%
“…Kim et al reported glucosyltransferase-independent disruption of focal adhesion formation (32) and production of reactive oxygen species (33) in colonocytes induced by TcdA. Most recently, several studies have indicated that neither the CPD nor GTD enzymatic activities of TcdB are required for cellular intoxication at high toxin doses (34)(35)(36), whereas the hydrophobic region in the transloca-tion domain and GTD are important for the rapid induction of cell death (37,38). These studies utilize toxin mutagenesis, which is well known to alter protein active-site specificity or conformational integrity (39).…”
mentioning
confidence: 99%
“…A plasmid-based approach to produce a recombinant toxoid in a TcdA ¡ TcdB ¡ strain of C. difficile has also been utilised. 125 As expected, the TcdA and TcdB toxoids expressed in this plasmid system were significantly less toxic to human IMR-90 cells. Such formalin-inactivated antigens elicited a protective effect in hamster models of CDI.…”
Section: Recombinant Vaccinesmentioning
confidence: 65%
“…Such formalin-inactivated antigens elicited a protective effect in hamster models of CDI. 125 Wang et al developed a chimeric toxin vaccine, consisting of immunogenic epitopes from both TcdA and TcdB. 126 In essence, the receptor binding domain of TcdA replaced that of TcdB and the resulting chimeric toxin displayed strong immunogenic potential.…”
Section: Recombinant Vaccinesmentioning
confidence: 99%